Calculation of the Spatial Flooding Intensity with Unit Flood Response Method in the Tangrah Watershed, Iran - Masoumeh Gharib; Baharak Motamedvaziri; Bagher Ghermezcheshmeh; Hasan Ahmadi (Salehan Institute of Higher Education, 2017)
Increased flooding in recent years indicates that most parts of the country are subjected to periodic and destructive flood attacks. Therefore, the identification of high-risk areas with potential runoff production within a watershed area is one of the most important measures in flood control and reduction of the damage caused by it. In this study, the quasi-distributional ModClark method was employed to simulate the hydrograph of flooding, and the unit flood response method was applied to determine the intensity of flooding of different areas of the Tangrah watershed, Iran. For this purpose, the ModClark model was first calibrated and verified. Thereafter, the design of rainfall with 50 and 100-year return periods ( ) was extracted at the Tangrah station and the design flood was calculated with the above-mentioned return periods. By combining the curve number layers, slope, precipitation, and flow distance, homogeneous units were obtained in terms of the flood. The effect of each homogeneous unit on the total watershed output was obtained by the removal of each unit and implementation of the rainfall-runoff model. According to the 100-year return runoff production potential, homogeneous units of 116 with a fi (0.54 m3/ s. km2) were identified as the most effective cell in the Tangrah watershed area, which could be explained by the soil type, vegetation, and other physical factors of these units.